Pengaruh Technology Acceptance Model pada SPT Tahunan OP terhadap Kepatuhan Wajib Pajak - Ahmad Arifin Ilham; Sri Andriani (JURNAL RISET AKUNTANSI JAMBI, 2025)
This study analyzes the effect of ease of use, usefulness, and security of the Individual Income Tax (PPh) Annual Tax Return (SPT) system through the Coretax application on taxpayer compliance, particularly among MSMEs in Malang City. Although MSMEs contribute significantly to Indonesia's GDP, their tax compliance rate remains low. The study used a descriptive quantitative approach with a sample of 102 respondents taken by simple random sampling from the population of MSMEs registered at the Malang City Trade and Industry Office. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression referring to the Technology Acceptance Model (TAM). The results showed that perceptions of usefulness and security had a significant positive effect on taxpayer compliance, while perceptions of ease of use had a negative effect. Simultaneously, the three independent variables explained 91.9% of the variation in tax compliance. These findings provide implications for tax authorities to optimize Coretax features by focusing on increasing system benefits and security and simplifying the interface to improve MSME tax compliance.